2012
DOI: 10.1371/journal.pone.0038646
|View full text |Cite
|
Sign up to set email alerts
|

Personal Decision-Making Criteria Related to Seasonal and Pandemic A(H1N1) Influenza-Vaccination Acceptance among French Healthcare Workers

Abstract: BackgroundInfluenza-vaccination rates among healthcare workers (HCW) remain low worldwide, even during the 2009 A(H1N1) pandemic. In France, this vaccination is free but administered on a voluntary basis. We investigated the factors influencing HCW influenza vaccination.MethodsIn June–July 2010, HCW from wards of five French hospitals completed a cross-sectional survey. A multifaceted campaign aimed at improving vaccination coverage in this hospital group was conducted before and during the 2009 pandemic. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…In agreement with the results of the study by Kaboli et al [ 28 ], we did not find that nurses had lower coverages than family physicians, although other studies have found the opposite [ 5 - 7 , 17 , 20 , 33 , 36 ]. Likewise, we found that paediatricians had higher coverages, confirming the results of the study by Bertin et al [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the results of the study by Kaboli et al [ 28 ], we did not find that nurses had lower coverages than family physicians, although other studies have found the opposite [ 5 - 7 , 17 , 20 , 33 , 36 ]. Likewise, we found that paediatricians had higher coverages, confirming the results of the study by Bertin et al [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This coverage was close to the 58% found by Blasi et al [ 32 ] in a survey carried out among members of two European societies and to that found by Bouadna et al (58% for physicians and 30% for other healthcare workers) in a French hospital study [ 33 ]. Compared with other studies in primary healthcare carried out in Spain, the coverage was somewhat higher than the 44.2% and 19.6% obtained by Ortiz et al [ 14 ] and Jimenez et al [ 4 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Both general population and HCWs showed a low grade of acceptance of influenza vaccination due to public scepticism, low trust in health’ authorities recommendation, low perceived benefits of influenza vaccination for the individual and the community [ 11 14 , 19 ]. Furthermore, personal reasons for not getting influenza vaccination include doubt about safety of vaccines, fear of adverse effects, feeling of not being at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several investigations have been performed at a local level to analyze the healthcare workers’ educational deficiencies and the correlations with the actions taken by public health authorities to implement vaccination rates, however no study has systemized and analyzed such results at a nationwide level [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%